VD_FINDINFO HC / 2015 / 1059 vom 5. November 2015 - VD Tribunal cantonal (2015)
MODÉRATION, HONORAIRES, AGENT D'AFFAIRES, TARIFEN GÉNÉRAL | 7 al. 2 LPAg, 9 al. 3 LPAg, 95 LPA-VD, 98 LPA-VD, 10 TDC, 20 TDC